The Influence of Service Quality, Customer Satisfaction, and Brand Image on Consumer Loyalty in Elzatta Customers - Makadina, Frendy Delba; Muthohar, Muchsin (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to identify the influence of service quality, customer satisfaction, and brand image on customer loyalty among Elzatta consumers. The study utilizes non-probability convenience sampling technique for sample selection. The primary data collected for this study consists of 250 respondents. The statistical analysis technique employed in this study is Structural Equation Modeling (SEM) using SmartPLS software version 3.2.9. The results of the data analysis indicate that service quality has a positive and significant influence on customer satisfaction, brand image, and customer loyalty. Customer satisfaction has a positive and significant influence on brand image and loyalty, and brand image also has a positive and significant influence on customer loyalty.